7-Deaza-2`-deoxyguanosine allows PCR and sequencing reactions from CpG islands. Issue 1 (1st February 2002) - Jung, A; Ruckert, S; Frank, P; Brabletz, T; Kirchner, T
Abstract : CpG islands are GC rich sequences that are found in the promoters of many genes in higher eukaryotes. They contain a high frequency of CG dinucleotides, which are substrates for DNA methylases. Methylation leads to transcriptional silencing of promoters. Owing to their high GC content CpG islands exhibit strong base–base interactions, which lead to superstructures and consequently to regions with higher melting temperatures. Therefore, Taq polymerases (especially sequenases) fall off their templates, causing premature termination of the polymerase chain reaction (PCR) or sequencing reactions. The results from such reactions are thus insufficient for further analysis. Therefore, we have evaluated the use of 7-deaza-2`-deoxyguanosine for PCR amplification of the human p16 INK4A promoter and sequencing of HUMARA exon 1 PCR products. Our results show that the addition of 7-deaza-2`-deoxyguanosine significantly improves results, particularly when small amounts of poor quality DNA are available as starting material.